Medicine and the Inquisition in the Early Modern World - Donato, Maria Pia (BRILL, 2019)
This volume includes the articles originally published in Volume XXIII, Nos. 1-2 (2018) of Brill's journal 'Early Science and Medicine' with one additional chapter by Timothy D. Walker and an updated introduction.00'Medicine and the Inquisition' offers a wide-ranging and nuanced account of the role played by the Roman, Spanish and Portuguese Inquisitions in shaping medical learning and practice in the period from 1500 to 1850.0Until now, learned medicine has remained a secondary subject in scholarship on Inquisitions. This volume delves into physicians' contributions to the inquisitorial machinery as well as the persecution of medical practitioners and the censorship of books of medicine.0Although they are commonly depicted as all-pervasive systems of repression, the Inquisitions emerge from these essays as complex institutions. Authors investigate how boundaries between the medical and the religious were negotiated and transgressed in different contexts. The book sheds new light on the intellectual and social world of early modern physicians, paying particular attention to how they complied with, and at times undermined, ecclesiastical control and the hierarchies of power in which the medical profession was embedded.